2012
DOI: 10.1007/s13364-012-0075-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the barrier to gene flow between phylogeographic lineages of the common hamster Cricetus cricetus

Abstract: In anthropogenically disturbed habitats, natural barriers still exist and have to be recognized, as they are important for conservation measures. Areas of phylogeographic breaks within a species are often stabilized in inhospitable regions which act as natural barriers. An area of contact between phylogeographic lineages of the common hamster (Cricetus cricetus) was found in the Małopolska Upland in Poland. A total of 142 common hamsters were captured between 2005 and 2009. All hamsters were genotyped at 17 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…As shown in Figure 2, an obvious correlation can be inferred between the levels of genetic diversity and the population density. Our results are in accordance with studies in other species in which a similar correlation was found (Aspi et al 2006;Berthier et al 2006;Eckert et al 2008;Frankham 1996;Furlan et al 2012;Montgomery et al 2000;Wang et al 2013), including other rodents (Krebs 2013) and hamster species (Romanenko et al 2007), like the greater longtailed hamster (Dong et al 2010;Xie and Zhang 2006;Xu et al 2013a;Xue et al 2014), the golden hamster (Karsten et al 2005), and the common hamster (Banaszek et al 2012;Neumann et al 2005). Similarly, the genetic diversity of the striped hamster has experienced a trend of continuous decline in recent years.…”
Section: Genetic Diversity and Genetic Differentiationsupporting
confidence: 92%
“…As shown in Figure 2, an obvious correlation can be inferred between the levels of genetic diversity and the population density. Our results are in accordance with studies in other species in which a similar correlation was found (Aspi et al 2006;Berthier et al 2006;Eckert et al 2008;Frankham 1996;Furlan et al 2012;Montgomery et al 2000;Wang et al 2013), including other rodents (Krebs 2013) and hamster species (Romanenko et al 2007), like the greater longtailed hamster (Dong et al 2010;Xie and Zhang 2006;Xu et al 2013a;Xue et al 2014), the golden hamster (Karsten et al 2005), and the common hamster (Banaszek et al 2012;Neumann et al 2005). Similarly, the genetic diversity of the striped hamster has experienced a trend of continuous decline in recent years.…”
Section: Genetic Diversity and Genetic Differentiationsupporting
confidence: 92%
“…Genetic studies on small Polish populations have revealed a contact zone between two haplogroups of this species in the Małopolska Upland (southern Poland; Fig. 1d, Table 1; Banaszek et al 2012). Of these, the Pannonian lineage probably originated from the Carpathian refugium, while the E1 lineage originated from the Russian Plains or Ukrainian steppe (Banaszek et al 2012).…”
Section: Small Mammalsmentioning
confidence: 99%
“…Therefore, SSRs were only used as an additional source of information about genetics of examined taxa since simultaneous use of both types of markers is common practice that allows for comprehensive phylogeographic and population genetic analyses (especially when a study has conservation implications). As mtDNA data are available for all animals examined, and either AFLPs and/or plastid data are available for all plants, it was possible to analyse and compare data within animals and within plants in a similar way ( Galarza et al 2015; Cricetus cricetus (Cricetidae): Neumann et al 2004Neumann et al , 2005Banaszek et al 2010Banaszek et al , 2011Banaszek et al , 2012Schroeder et al 2014. (Color figure online) We examined all of these data to identify the following characters of the selected steppic taxa:…”
Section: Elaboration Of Genetic Datamentioning
confidence: 99%
“…The phylogeography of continental species was partly included in the reviews of Stewart et al (2010) and Varga (2010), but mostly on the basis of chorological data, making the steppededicated parts of the above papers more thought-provoking than reviewing. The general disregard for continental elements in reviews about the phylogeography of European species could be explained by the relatively recent arrival of studies on this group (with the Table 1 Steppic species examined in the meta-analysis with their systematic affiliation, references of papers reviewed, molecular markers used and range covered in these Gvozdik et al (2012), Zinenko et al (2015) seq ( Neumann et al (2004Neumann et al ( , 2005, Banaszek et al (2010Banaszek et al ( , 2011Banaszek et al ( , 2012, Schroeder et al (2014) seq (mtDNA), msats AT,CZ,DE,HU,PL,RO,RU,SK,UA…”
Section: Introductionmentioning
confidence: 99%